The Influence Of Tax Understanding, Tax Sanctions, And Tax Awareness With Tax Socialization As Moderating Variable In Jayawijaya Papua - gerrits, Tien Vanenssia Wehelmina; Roekhudin; Iqbal, Syaiful (The International Journal of Accounting and Business Society, 2024)
Purpose—This study sought empirical evidence of the effect of tax understanding, tax sanctions, and tax awareness on tax compliance and added moderation variables that can affect tax compliance in Jayawijaya Papua. Socialization is the selected variable that becomes the moderating variable. Design/methodology/approach — the methodology used in this study is quantitative research with a survey approach. Findings—Based on the results of data analysis and discussions carried out in this study, it can be concluded that tax understanding, tax sanctions, and tax affect land and building tax compliance in Jayawijaya Papua. These results can help the Jayawijaya authorities understand how socialization affects how well-informed Jayawijaya taxpayers are about tax laws and processes. Taxpayer understanding and awareness of their tax obligations will increase through regular outreach, increasing taxpayer compliance in Jayawijaya. Practical implications — The results of this research are expected to be taken into consideration by the authorities (Bappenda) in finding solutions or innovations in conducting tax socialization to local taxpayers so that it will increase the compliance of the Jayawijaya people in paying their land and building tax obligations through socialization. The results of this study are also expected to provide a reference for all parties in efforts to develop and strengthen the capacity of related agencies through strategic policies in utilizing regional potentials so that they have implications for people's lives in general. Originality/value—This study presents a phenomenon related to land and building taxes in Jayawijaya Papua. It analyzes taxpayers and identifies the causes of low taxpayer compliance in Jayawijaya Papua. The study reveals facts related to taxpayer compliance so that it can provide input to the government in implementing regional financial management. Keywords — tax understanding; tax sanction; tax awareness; tax compliance; tax socialization Paper type — Survey study